Etiology and treatment modalities in epistaxis - Balakrishnan, Sreelakshmi; Manonmony, Sajilal; Prakash, Nidhin; Renjit, Rejee Ebenezer; Mohan, Avinash (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Epistaxis or 'hemorrhage from the nose' is a frequent presentation in the otorhinolaryngologic emergency and both conservative and surgical modalities have been used in the treatment. The present study was undertaken to estimate the proportion of patients with epistaxis who are effectively managed with conservative modalities. Methods: A total of 60 patients (39 males and 21 females) between 18 and 70 years, with epistaxis were studied in the department of otorhinolaryngology and emergency units of Dr. Somervell Memorial C.S.I Medical College Hospital, Karakonam, Thiruvananthapuram, between November 2018 and April 2020. The data, that is the proportion of patients who are effectively managed with conservative modalities, was entered into Microsoft - Excel sheet and analysis was done using statistical package for social sciences (SPSS) software trial version. Results: Out of 60 cases of epistaxis, 81.67% were effectively controlled by conservative management like general first aid (43.33%), chemical cautery (10%), and nasal packings via anterior (21.67%) and posterior (6.67%). Conclusions: In 81.67% nasal bleeding was effectively controlled by conservative treatment measures and in 18.33% surgical measures were required.